Incidence and attributable costs of ventilator-associated pneumonia (VAP) in a tertiary-level intensive care unit (ICU) in northern India - Ashu Sara Mathai; Atul Phillips; Paramdeep Kaur; Rajesh Isaac (Elsevier, 2015)
Background: Ventilator-associated pneumonia (VAP) is the most common nosocomial infection acquired by patients in the intensive care unit (ICU). However, the economic effects of such infections remain unclear particularly in developing countries. Methods: Patients who were mechanically ventilated for more than 48 h in the ICU were studied for the occurrence of VAP. Total drug costs and hospital costs were noted, and attributable costs were calculated after adjusting for potential confounders. Results: Ninety-five (38%) patients who were ventilated for more than 48 h developed VAP, which resulted in an incidence of 40.1 VAP infections/1000 mechanical ventilation days. The patients with VAP experienced significantly longer hospital stay [21 (IQ = 14-33) days versus 11 (IQ = 6-18) days, P < 0.0001)] and incurred greater hospital costs [USD $6250.92 (IQ = 3525.39-9667.57) versus $2598.84 (IQ = 1644.33-4477.65), P < 0.0001]. Multiple regression analysis revealed that the cost-driving factors in our study population were the occurrence of VAP infections (P < 0.0001) and the duration of hospital stay (P < 0.0001). The attributable cost of VAP infection was calculated to be USD $5200 (95% CI = 3245-7152). Conclusion: We conclude that VAP significantly increases the costs of treatment in low-income developing countries. This study highlights the need to implement urgent measures to reduce the incidence of this disease in ICUs. Keywords: Ventilator-associated pneumonia, Attributable costs, Intensive care unit